The Effect of Giving Moringa Leaf Flour (Moringa oleifera) in Feed as Feed Additive on Carcass Quality of Super Kampung Chicken (Gallusgallus domesticus L. Joper variation) - Wahyu Nainggolan; Nurjama’yah br Ketaren; Usman Budi (Jurnal Peternakan Integratif, 2025)
Super kampung chicken is a descendant of kampung chicken, bangkok chicken, or other types of local chicken that are crossed with broiler chickens. In addition to genetic factors and feed management, the use of natural ingredients as feed additives can affect the quality of super kampung chicken meat. Feed additives are materials that are not included in food substances that are added to feed in small amounts and aim to stimulate growth and increase feed efficiency. With various studies in the selection of quality feed raw materials that are used as feed additives, easy to obtain, and cheap to meet the needs of super kampung chicken, namely moringa leaves. The design used in this study was a Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatments consisted of PO (Ration does not contain moringa leaf flour), Pl (Ration contains 6% moringa leaf flour), P2 (Ration contains 9% moringa leaf flour), P3 (Ration contains 12% moringa leaf flour), The parameters observed were final body weight, carcass weight and carcass percentage. The results showed that moringa leaf flour was significantly different on the final body weight, carcass weight and carcass percentage. The best results were obtained in the Pl treatment, namely the ration containing 6% moringa leaf flour which was able to increase the final body weight by 1178.27 g, carcass weight by 759.40 g and carcass percentage by 64.50.